Unidirectional transfer of prostaglandin endoperoxides between platelets and endothelial cells. - Schafer, A I (1984)
An important determinant of platelet-vessel wall interactions is the local balance of production of endothelial prostacyclin (PGI2) and platelet thromboxane (TX) A2, labile eicosanoids with opposing effects on hemostasis. Disputed evidence suggests that platelet-derived prostaglandin endoperoxide intermediates may be utilized as substrates for vascular PGI2 synthesis. Using several different approaches, we have found that platelets can transfer endoperoxides to cultured endothelial cells for efficient conversion to PGI2, but a reciprocal transfer of endothelial endoperoxides for utilization by platelet thromboxane synthetase does not occur under the same experimental conditions. However, platelets can utilize arachidonic acid released by endothelial cells for lipoxygenase metabolism. We have directly demonstrated the production of [3H]6-keto-PGF1 alpha (the breakdown product of [3H]PGI2) by aspirin-treated endothelial cells in the presence of platelets stimulated with [3H]arachidonic acid. In coincubation experiments using either arachidonate or ionophore A23187 as a stimulus, radioimmunoassay of the net production of arachidonic acid metabolites showed that 6-keto-PGF1 alpha generation by aspirin-treated endothelial cells in the presence of platelets may actually exceed its generation by uninhibited endothelial cells alone. In functional assays, platelet aggregation was inhibited in the presence of aspirin-treated endothelial cells after stimulation with either arachidonate or ionophore A23187. In contrast, the inverse experiments, using aspirin-treated platelets and uninhibited endothelial cells, failed to demonstrate platelet utilization of endothelial endoperoxides for TXA2 production by any of the above methods. These studies thus provide evidence that efficient unidirectional transfer and utilization of platelet-derived endoperoxides for endothelial PGI2 production can occur. This process may serve to amplify PGI2 generation adjacent to areas of vascular injury and permit tight localization of platelet plug formation at these sites.